Implementasi pembiayaan murabahah pada PT. Pegadaian Syari’ah Unit Karang Pilang Surabaya - Nurjanah, Nanda Alifia (Maliki Interdisciplinary Journal, 2023)
PT. Pegadaian Syariah Unit Karang Pilang Surabaya employs a financing product called Precious Metals Murabahah for Perpetual Investment (MULIA). This product is a form of buying and selling financing in the form of cash or credit in accordance with Islamic principles. The purpose of this research is to identify the factors that affect margins in murabaha financing and the application of sharia principles to the Standard Operating Procedures. The results of this study indicate that in setting the margin on Murabahah financing, Islamic values ​​have been considered and the application of Standard Operating Procedures has implemented sharia principles.